Trade costs and impacts of trade facilitation on manufacturing exports by Thailand - Piya Wongpit (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2013)
The improvement of international trade in recent years has been influenced by the reduction of trade costs. The attention of international trade is to minimize trade costs through tariffs, trade facilitation and trade logistics, both inbound and outbound. As one of the emerging economies in international trade, Thailand's economy depends much on trade and therefore the Government has been attempting to eliminate all trade barriers. Since Thailand's manufacturing trade amounts to some 90% of total trade, trade costs must play a significant role in such trade. The objective of this paper is to estimate trade costs of manufacturing exports between Thailand and its trading partners, and to analyse the impacts of trade facilitation on such exports by Thailand. The study first estimates the comprehensive trade costs of the manufacturing industry for Thailand and 23 trading partners from 1999 to 2010 by using the Chen and Novy (2009) model. Then the comprehensive trade costs are decomposed into their component parts. The impacts of trade facilitation, including documentation and time involved in the export and import process, and the liner shipping connectivity index on manufacturing exports by Thailand are also discussed. The results indicate that manufacturing trade costs have continuously decreased over time due to the reduction of tariff and non-tariff costs. The manufacturing trade costs between Thailand and Singapore are the lowest while between Thailand and Japan, the most important trading partner of Thailand, they are the third lowest. On the other hand, the manufacturing trade costs between Thailand and the European Union are relative high due to the distance between the two regions. Distance contributed the highest proposition of trade costs. Trade facilitation, such as the reduction of the number of documents and time involved in manufacturing exports and imports have also been an important factor associated with trade costs in recent years. The trade facilitation factor has had an impact on manufacturing exports by Thailand and has become more important in the country's manufacturing trade. The results of this study are robust and exhibit consistency with previous studies that have found that the improvement of trade facilitation enhances manufacturing exports by Thailand.
Keywords: F14; 330; Trade costs; trade facilitation; manufacturing exports; Thailand